Konsumsi dan Gaya Hidup: Interseksi Kelas di Asia Tenggara - Linggar Rama Dian Putra (Jurnal Kajian Wilayah, 2013)
This paper discusses on the current developments in the cities of Southeast Asia by looking at the expansion of the global market as an independent variable that give an impact on the consumption patterns of urban communities in Southeast Asia. Although the wave of globalization has swept the region from few decades ago, but since the 2000s the cities in Southeast Asia experience significant changes due to the overwhelming stream of mass commodity products. The emergence of modern business and shopping district at the heart of major cities in Southeast Asia become a common phenomenon that evolves and has a contribution in shaping the face of urban areas in Southeast Asia. The presence of a mass commodity also contributes in shaping the discourse of lifestyle and consumption then defining the atmosphere of urban and social dynamics in the public space. This paper demonstrates the changes in the landscape and its impact on a culture of consumption that occurred in the cities in Southeast Asia. Focus area as the case study in this paper is Surabaya (Indonesia) and Kuala Lumpur (Malaysia)